Menstrual cup awareness and preference among college going women in Tenkasi district, Tamil Nadu: a cross sectional survey - Fathima Kani, M.; Varghese, Achamma (International Journal of Research in Medical Sciences, 2024)
Background: Menstrual hygiene is an important aspect of women’s health. Every month, half of India's population experiences menstruation. However, still India has strong sociocultural taboos concerning menstruation. Menstruation cups (MC) have become more and more well-liked as an affordable and environmentally responsible replacement for conventional menstruation products in recent years. In India, they are still not widely recognized because of cultural constraints. The primary objective of this study was to identify the MC Awareness and preference among college-going women. Methods: This descriptive cross-sectional study was conducted among college-going women in Tenkasi district, Tamil Nadu, India between June 2023 and August 2023 with a predesigned structured questionnaire. The sample size of the study was 120 college-going women included in this study. SPSS software was used for the data analysis. Results: The participant's mean age was 19.08±3.14 years. More than half of the participants had low awareness of MC (56.6%). None of the participants were using MC as the choice for menstrual management currently. The main reasons for not preferring the MC as the future choice were leakage (65%), difficulty to use (58.3%), infection (56.6%), it might produce complications (56.6%), and pain and discomfort (50%). Conclusions: The awareness and future preferences for the MC were low. Young educated women have less awareness and less preference for MC shows the necessity of the creation of awareness programs at the community level. The healthcare sector needs to take the necessary steps to increase the utilization of MC to follow proper menstrual hygiene.